THE RUNOFF’S BEHAVIOR TO DIFFERENT LAND USES IN WATERSHEDS AT NORTHWESTERN PARANA, BRAZIL - Costa Filho, Lysias Vellozo; Rizzi, Nivaldo Eduardo (Floresta, 2016)
The study attempted to evaluate the effectiveness of the forestry ecosystem on the maintenance of the hydrological processes, which participated on soil’s erosion. Aimed to support the land use planning and soil’s erosion control works. The work was done through of a simulated rainfall experiment replicated on three watersheds of the Northwest region of the State of Paraná, into four land uses. The experiment was developed by comparing the runoff’s behavior of the land uses: forest and three agricultural crops (coffee, cassava and pasture). The results showed greatest infiltration coefficient for soils under forest, with significant difference to other land uses studied. These differences showed that unit area with forest cover resulted in 9,71 times less runoff than area with pasture, 7,86 times less runoff than area with coffee, and 5,56 times less runoff than area with cassava. The results show the forest’s potentiality to improve the infiltration processes, showing responses that virtually are not possible to be superseded by the management practices adopted on the other cropping systems studied. The study, to define the range of the forest’s effect on its environment, is characterized as essential to planning of the forest cover regarding to size area, and spatial distribution.